Implementasi Pendekatan Kontekstual dalam Pembelajaran Fikih di Pondok Pesantren Nihayatus Salikin - Cofsoh, Yanuba Arifatul; Bahtiar, Edi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2025)
This study aims to determine the application of the contextual approach in learning fiqh at the Nihayatus Salikin Islamic boarding school. The approach used is a qualitative approach with the type of case study. The data collected came from supporting documents, interviews and participatory observation which were then analyzed using the reduction stage which was then presented in the form of descriptive narratives and conclusions were drawn. Triangulation used in testing the validity of data is source triangulation, namely by comparing two data that have been obtained. The results showed that the implementation of the contextual approach in learning fiqh at the Nihayatus Salikin Islamic boarding school was carried out using three stages. First, planning in the form of selecting books that are used as guidelines in learning. Second, implementation by using three learning methods, namely the bandongan, sorogan and deliberation methods which are integrated with the components of the contextual approach, including constructivism, discovery, questioning, learning communities, modeling, reflection and authentic assessment. Third, the evaluation is carried out using written tests and direct observation of the santri's involvement in applying the material that has been learned.